Micro-Scale Liquid Smoke Extraction as a By-Product from Coconut Shell Charcoal Production in Kotabatu Village - Uswatun Hasanah; Ade Heri Mulyati; Lenny Heliawati (Research Collaboration Community (RCC), 2022)
Liquid smoke is produced from the pyrolysis process and condensation from the coconut shell waste combustion process. This liquid smoke is known to have a high level of polyphenol content and is used as a rubber processing, deodorizing, and wood preservative to make it resistant to termites. In addition, it can also be used as an insecticide for plants. This community service is carried out to design and manufacture a micro-scale liquid smoke pyrolysis machine, which is expected to reduce the amount of smoke produced during the charcoal burning process, also to help partners create an additional type of product, namely liquid smoke. for plant insecticides so that it will increase partners' monthly income. The method that will be used in achieving this goal is to provide training and practice to partners on how to process cranium waste other than into charcoal, namely into liquid smoke as an insecticide in plants.